Obstetric Sepsis: Understanding, Prevention, And Management (Eurasian Medical Research Periodical, 2023)
This article explores the critical topic of obstetric sepsis, a life-threatening condition that poses significant risks to maternal and infant health. The article delves into its causes, symptoms, risk factors, prevention, management, and the barriers hindering effective treatment. Additionally, the article highlights the importance of research, awareness campaigns, collaboration, and advocacy in addressing obstetric sepsis and improving maternal healthcare outcomes.